2018
DOI: 10.1177/0145445518820036
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Psychological Flexibility: A Latent Class Analysis of the Acceptance and Commitment Therapy Model

Abstract: There exists uncertainty for clinicians over how the separate subcomponent processes of psychological flexibility, a core construct of the Acceptance and Commitment Therapy model, interact and influence distress experienced. The present study ( N = 567) employed latent class analysis to (a) identify potential classes (i.e., subgroups) of psychological flexibility based on responses on measures of key subcomponent process and (b) examine whether such classes could reliably differentiate levels of self-reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 85 publications
(164 reference statements)
3
21
2
1
Order By: Relevance
“…Using passive strategies to overcome stress prevents new learning experiences, for instance, that problems are not as great as imagined or out of control (Craske et al, 2014). This study's findings differ from those of Tyndall et al (2020), who found that single participants had the highest levels of psychological flexibility. Family support (not friends and close people) is considered more meaningful in providing certainty and security, a concrete need during a pandemic (Liu et al, 2020).…”
Section: Discussioncontrasting
confidence: 82%
“…Using passive strategies to overcome stress prevents new learning experiences, for instance, that problems are not as great as imagined or out of control (Craske et al, 2014). This study's findings differ from those of Tyndall et al (2020), who found that single participants had the highest levels of psychological flexibility. Family support (not friends and close people) is considered more meaningful in providing certainty and security, a concrete need during a pandemic (Liu et al, 2020).…”
Section: Discussioncontrasting
confidence: 82%
“…According to this model, people who have higher levels of psychological well-being can establish an open and flexible contact with their own internal and external states (environmental) and engage themselves in committed actions related to personal values. Psychological flexibility has been strongly associated with several positive psychological outcomes, such as increased psychological well-being, reduced stress, anxiety, and depressive symptomatology (Bardeen et al, 2014;Francis et al, 2016;Tyndall et al, 2020). In opposition, decreased levels of psychological flexibility form the basis of psychological distress characterized by difficulties in emotional and behavioral regulation (Masuda and Tully, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This, in turn, could trigger more avoidance, in a sort of vicious cycle. There is broad evidence that experiential avoidance and, more generally, the lack of flexibility regarding private events is associated with emotional distress and poor mental health and quality of life [ 8 , 9 , 10 , 11 , 12 ]. Indeed, the explicit goal of ACT is to enhance psychological flexibility [ 5 , 6 ] by teaching clients to be more open to experiencing private events as they arise (rather than attempting to control them) in leading a life driven by personally chosen values.…”
Section: Introductionmentioning
confidence: 99%